Promising Roles of Exosomal microRNAs in Systemic Lupus Erythematosus - Wang, Wenqian; Yue, Chenran; Gao, Sheng; Li, Shuting; Zhou, Jianan; Chen, Jiaqing; Fu, Jiahong; Sun, Weijian; Hua, Chunyan (Frontiers in Immunology, 2021)
Systemic lupus erythematosus (SLE) is a prototypic autoimmune disease characterized by the loss of immune tolerance. Lupus nephritis (LN) is still a major cause of the morbidity and mortality of SLE. In clinical practice, diagnosis, and therapy of SLE is complicated and challenging due to lack of ideal biomarkers. Exosomes can be detected from numerous kinds of biological fluids and their specific contents are considered as hallmarks of autoimmune diseases. The exosomal miRNA profiles of SLE/LN patients significantly differ from those of the healthy controls making them as attractive biomarkers for renal injury. Exosomes are considered as optimal delivery vehicles owing to their higher stable, minimal toxicity, lower immunogenicity features and specific target effects. Endogenous miRNAs can be functionally transferred by exosomes from donor cells to recipient cells, displaying their immunomodulatory effects. In addition, it has been confirmed that exosomal miRNAs could directly interact with Toll-like receptors (TLRs) signaling pathways to regulate NF-κB activation and inflammatory cytokines secretion. The present Review mainly focuses on the immunomodulatory effects of exosomal-miRNAs, the complex interplay between exosomes, miRNAs and TLR signaling pathways, and how the exosomal-miRNAs can become non-invasive diagnostic molecules and potential therapeutic strategies for the management of SLE.